An exploration of South African corporate communication practices and trends - Meintjes Corne; Ilse Niemann-Struweg; Gideon de Wet (Communicare)
This study explored the status of corporate communication in selected South African companies. The main purpose of the study was to determine the levels of corporate communication knowledge and practical abilities of top corporate communication professionals. The research design adopted was a mixed method approach utilising a sequential transformatory model. The sample, selected through purposive and convenience sampling, consisted of twenty-six professionals drawn from a wide range of businesses and sectors in South Africa. The study indicates that corporate communication professionals deal with stakeholder-relationship management and perceive their roles as being strategic, then managerial, and lastly technical in nature, which is however often not practically applied. Furthermore, the study alludes to the fact that the corporate communication professionals concerned had a basic understanding of the strategic issues where the strategic implications of issues of publicity, company image and reputation were seemingly grasped by professionals. This highlights the need for continuous training in corporate communication - particularly at the strategic level- although it is apparent that corporate communication professionals need to be schooled continuously in a fundamental understanding and analysis of power relations, ranging from the most basic interpersonal levels to the socio-political contexts. Such training may allude to how these contexts, these relations, affect the way in which practitioners put it into practice. The study forms part of an international benchmarking survey that aims to contribute to a better understanding of corporate communication best practices worldwide.